Análise de viabilidade populacional do muriqui, Brachyteles hypoxanthus (Primates: Atelidae), em fragmentos de Mata Atlântica de Santa Maria de Jetibá - Espírito Santo - Coutinho, Bruno Rocha (2007)
Habitat lost and habitat fragmentation are in the most important processes related to species extinction around the world. Because of isolation in habitats fragments, those processes can reduce the population size and modify remaining subpopulations’spatial distribution. This situation is occurring with the northern muriqui(Brachyteles hypoxanthus), one of the most 25 most endangered primates of the world. This species have been hunted for centuries because of this great size. In a region of Espírito Santo state, Southern Brazil, there are many northern muriqui subpopulations that survive in small isolated fragmented habitats where somefemales became lonely after they disperse because they can’t find another group todisperse. This research focused on: (1) subpopulations vulnerability on absent of demography interactions, (2) dispersal fluency of females on the populations’ viability, (3) stochastic factors (demographic, environmental, and genetics) that arecritical for the species persistence in a fragmented landscape, and (4) relative riskestimation faced by the subpopulations due species biological extrinsic processes,like hunting. I conducted a population viability analysis (PVA) using the computerpackage VORTEX. I used four years of demographic data from Espírito Santo’s Muriqui Project (Projeto Muriqui) and biological data from Karen B. Strier’s researches. PVA’s results demonstrated that all nine subpopulations showed high probability of extinction, and at least 25% heterozygosity lost for 50 years. The results also demonstrated that six of nine subpopulations are in decline. These subpopulations presented negatives growing rates (r < 0). 21 and 34 years were the subpopulations’ median extinction time, and seven and eight individuals/subpopulations were the final size. Female dispersal was the most critical factor on species survivorship. There were other factors that increased the speciesextinction probability when they were added to model: males’ sexual rate deviation,burning and adults female’s hunting. Young females can’t disperse because of the subpopulations isolation which cause high extinction vulnerability and northern muriquis subpopulations’ decline in a region of Espírito Santo. It’s necessary to arrange actions that minimize the isolation effects to increase the subpopulations viability in long term.